Correction the Bias of Odds Ratio resulting from the Misclassification of Exposures in the Study of Environmental Risk Factors of Lung Cancer using Bayesian Methods - Alireza Abadi; Bagher pahlavanzade; Keramat Nourijelyani; Seyed Mostafa Hosseini (Jorjani Biomedicine Journal, 2015)
Background & Objective: Inability to measure exact exposure in epidemiological studies is a common problem in many studies, especially cross-sectional studies. Depending on the extent of misclassification, results may be affected. Existing methods for solving this problem require a lot of time and money and it is not practical for some of the exposures. Recently, new methods have been proposed in 1:1 matched case–control studies that have solved these problems to some extent. In the present study we have aimed to extend the existing Bayesian method to adjust for misclassification in matched case–control Studies with 1:2 matching.